Modlitwa według Marka Eremity - Escure-Delpeuch, Émilie (Collectanea Theologica, 2019)
Mark the Ascetic is opposed to the Messalians. According to them, Satan inhabits the human heart from the fall and must be removed through constant prayer and expelled by receiving the Holy Spirit. For Mark the Ascetic it is the Holy Spirit who lives in the human heart from his baptism. The believer must be vigilant because Satan wants to come from outside to take the place of the Spirit. The continuous prayer is therefore not a way of getting closer to God. It is a weapon in a spiritual battle trying to distance us from God. It is even more than a weapon: it is love, because God and man are from the baptism in a love relationship which is expressed by prayer. Mark the Ascetic confronts the Messalians, who use the continuous prayer as a way of achieving salvation, a way which should result in the coming of the Holy Spirit. In this way, the Messalians “instrumentalise” prayer. The studies on Mark’s works, especially on his vocabulary to describe prayer, show his clearly defined position, which is completely different from the approach of the Messalians. Prayer for Mark the Ascetic is neither means, nor instrument. It is a sign of love, an exchange of intimate love with God. By reaching for wedding terminology, Mark clearly shifts the accenton love with God. Prayer becomes a place of love that is experienced in the heart of the faithful.